Current status and future perspectives on the evolution of cis-regulatory elements in plants. (February 2022) - Yocca, Alan E.; Edger, Patrick P.
Abstract: Cis-regulatory elements (CREs) are short stretches (∼5–15 base pairs) of DNA capable of being bound by a transcription factor and influencing the expression of nearby genes. These regions are of great interest to anyone studying the relationship between phenotype and genotype as these sequences often dictate genes' spatio-temporal expression. Indeed, several associative signals between genotype and phenotype are known to lie outside of protein-coding regions. Therefore, a key to understand evolutionary biology requires their characterization in current and future genome assemblies. In this review, we cover some recent examples of how CRE variation contributes to phenotypic evolution, discuss evidence for the selective pressures experienced by non-coding regions of the genome, and consider several studies on accessible chromatin regions in plants and what they can tell us about CREs. Finally, we discuss how current advances in sequencing technologies will improve our knowledge of CRE variation.